PERFORMANCE ANALYSIS OF PHOTOVOLTAIC SYSTEMS IN THE BRESTANICA THERMAL POWER PLANT - Bojan Vovčko (Journal of Energy Technology, 2024)
This paper deals with the performance ratio and energy yield of three photovoltaic systems (MFE TEB 1-3) in the Brestanica thermal power plant (TE Brestanica). The objective of this paper is to analyse these two parameters according to the different types of solar cells (amorphous/monocrys- talline silicon), non-ideal inclination, and azimuth angles of PV modules in different seasons. The analysis was made on the basis of operating data of MFE TEB 1-3 for the period from 2011 to 2016. Performance ratio is one of the most important parameters in the assessment of the quality of photovoltaic systems; it represents the ratio between the actual energy produced and the theoretical energy produced by a photovoltaic system and shows the proportion of energy that is available for transmission to the electricity network after deducting lost energy. In contrast, the energy yield represents the ratio between the actual energy produced and the nominal power of the photo- voltaic system. The results show a significant influence of temperature coefficient, as well as the inclination and azimuth angles of the PV modules on the performance ratio and the energy yield.